Is embryo a person? The dispute about artificial reproduction in Italy - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2007)
The public dispute about the methods of artificial reproduction has been led in Italy for many years, the most significant principle of the legislation from the year 2004 is the recognition of the human embryo as the human being from the very moment of the conception, the law in Italy forbids, among others, producing human embryos for scientific purposes, freezing and destroying human beings, using the methods of heterological artificial reproduction, the opponents of such legal regulations evoked the nationwide referendum in 2005 which - because of too poor turnout - did not manage to repeal the operative legislation.